2011
DOI: 10.1017/s1368980011002497
|View full text |Cite
|
Sign up to set email alerts
|

Food sources and correlates of sodium and potassium intakes in Flemish pre-school children

Abstract: Objective: The aim of the present study was to investigate dietary sources of Na and K intakes among Flemish pre-school children using multiple linear regression analyses. Design: Three-day estimated diet records were used to assess dietary intakes. The contribution to Na and K intakes of fifty-seven food groups was computed by summing the amount provided by the food group for all individuals divided by the total intake for all individuals. Setting: A random cluster sampling design at the level of schools, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Our finding of a high salt content in cheeses sold in the UK is similar to those observed in the USA,32 33 Australia,34 France,35 Belgium,36 Canada,37 New Zealand,38 South Africa39 and Brazil40 showing that high levels of salt in cheese is a global challenge.…”
Section: Discussionsupporting
confidence: 85%
“…Our finding of a high salt content in cheeses sold in the UK is similar to those observed in the USA,32 33 Australia,34 France,35 Belgium,36 Canada,37 New Zealand,38 South Africa39 and Brazil40 showing that high levels of salt in cheese is a global challenge.…”
Section: Discussionsupporting
confidence: 85%
“…26 Taken together, these findings suggest that milk consumption frequency contributes more efficiently to total K intake than does the consumption of fruit and vegetables in children. 14,15 Previous studies have already used UK excretions as a surrogate marker for K intake for studying associations between K intakes and health outcomes. 27,28 The relationship between ratios of UCa/Cr and Ca intakes and the potential of ratios of UCa/Cr as a surrogate marker for Ca intakes have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Previous studies also showed significant correlations between Ca intake and urinary potassium (UK) excretions. 16 Because of these reasons, one would expect a positive association between milk consumption frequencies and UCa and UK excretions.…”
mentioning
confidence: 99%
“…For example, milk and dairy products accounted for more than 60% of calcium intake while fruits were main food contributors to vitamin C intake. Among 696 Flemish preschoolers aged 2.5–6.5 years, milk, sweetened milk drinks, and cheese accounted for 59% of calcium intake [20] while sugared milk drinks, fried potatoes, milk, and fruit juices were main potassium sources [21]. In a sample of Australian preschool children with mean age of 3.5 years, key contributors to potassium intake were milk, yogurt, tropical fruit, and potatoes [2223].…”
Section: Discussionmentioning
confidence: 99%